1.
5x+13=3x-3
5x - 3x = -3 - 13
2x = -16
x = -16 : 2
x = -8
2.
5(2x-6)=10
2x - 6 = 10 : 5
2x - 6 = 2
2x = 2 + 6
2x = 8
x = 8 : 2
x = 4
3.
2x=-3
x = -3 : 2
x = -1,5
4.
12(x-2)=3(2x-8)+9
12x - 24 = 6x - 24 + 9
12x - 24 = 6x - 15
12x - 6x = 24 - 15
6x = 9
x = 9 : 6
x = 1,5
5.
3x(2x-5)=110
1.
5x+13=3x-3
5x - 3x = -3 - 13
2x = -16
x = -16 : 2
x = -8
2.
5(2x-6)=10
2x - 6 = 10 : 5
2x - 6 = 2
2x = 2 + 6
2x = 8
x = 8 : 2
x = 4
3.
2x=-3
x = -3 : 2
x = -1,5
4.
12(x-2)=3(2x-8)+9
12x - 24 = 6x - 24 + 9
12x - 24 = 6x - 15
12x - 6x = 24 - 15
6x = 9
x = 9 : 6
x = 1,5
5.
3x(2x-5)=110
5x-3x=-3-13
2x=-16
x=-8
2)5(2x-6)=10
10x-30 =10
10x=10+30
10x=40
x=40:10
x=4
3)2x=-3
x=-3:2
4)X =1.5
12(x-2)=3(2x-8)+9
12x-24=6x-24+9
12x-6x=9
6x=9
X=1.5
5)3x(2x-5)=110
3x=110 или 2х-5 =110
x= 110:3 2x =110+5
x=36 2/10 2x = 115
x=115:2
x=57,5
ответ:x1=36 2/10,x2=57,5
Удачных оценок)